Co-movement of commodity price indexes and energy price index: A wavelet coherence approach - Dervis Kirikkaleli; Hasan Güngör (Financial Innovation, 2021)
This research sheds light on the causal link between commodity price indexes, i.e., the Agricultural Raw Materials Price Index, Industry Input Price Index, Metal Price Index, and Energy Price Index, in the global market, using wavelet coherence, Toda-Yamamoto causality, and gradual shift causality tests over the period 1992M1 to 2019M12. Findings from the wavelet power spectrum and partial wavelet coherence reveal that: (1) there was significant volatility in the Agricultural Raw Materials Price Index, Industry Input Price Index, Metal Price Index, and Energy Price Index between 2004 and 2014 at different frequencies; and (2) commodity price indexes significantly caused the energy price index at different time periods and frequencies. It is noteworthy that the outcomes of the Toda-Yamamoto causality and gradual-shift causality tests are in line with the results of wavelet coherence.
Keywords: C3; E3; Q2; Q4; 650; Causality; Commodity price; Energy price; Wavelet coherence